Mood, Modality and Polarity Analysis of Winston S. Churchill’s Speech on Hitler’s Invasion of the U.S.S.R - Liping, Chen (Advances in Social Sciences Research Journal, 2017)
This paper analyzes a famous speech by Winston S. Churchill from the perspective of mood, modality and polarity with the aim to find out how interpersonal function is realized in the speech. It is found that the use of more declarative sentences, modal auxiliaries with high value and the negative polarity helps enforce the persuasive power of the political speech.